2019
DOI: 10.1136/bmjpo-2019-000534
|View full text |Cite
|
Sign up to set email alerts
|

Sleep problems, behavioural problems and respiratory health in children born extremely preterm: a parental questionnaire study

Abstract: ObjectiveTo explore whether children born extremely preterm (EPT) with different types of sleep problems had more behavioural and respiratory health problems than EPT children without sleep problems.DesignProspective, nationwide, questionnaire-based study. At 11 years of age, parents reported on four current sleep problems: difficulty falling asleep or frequent awakenings, snoring, daytime sleepiness and not recommended sleep duration (<9 hours). Behavioural problems were assessed by parents and teachers wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 43 publications
(53 reference statements)
0
12
0
Order By: Relevance
“…We identified 216 potentially eligible articles by reviewing titles and abstracts. Ultimately, 23 studies6–17 19–21 29–36 met the eligibility criteria and were included in the meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We identified 216 potentially eligible articles by reviewing titles and abstracts. Ultimately, 23 studies6–17 19–21 29–36 met the eligibility criteria and were included in the meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Table 1 summarises the authors, regions and population characteristics (eg, age and sex) of each study. Five cohort studies6 7 21 29 32 and 18 cross-sectional studies8–17 19 20 30 31 33–36 were included in the meta-analysis. Sleep disorders were assessed using questionnaires, face-to-face interviews or medical records.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Whilst the causal mechanisms implicating snoring in behavioural problems are unknown, parent-reported snoring two or more times a week was a stronger predictor of hyperactivity, inattention, psychosomatic, internalising and externalising problems than polysomnography-assessed and sleep-expert-scored apnea-hypopnea index severity in a community sample of children aged 6-10 years [21]. The only study in children born extremely preterm/ELBW showed that, at age 11, those children who snored had significantly greater emotional and conduct problems and there were trends towards higher hyperactivity/inattention and peer problems than extremely preterm/ELBW children who did not snore [22].…”
Section: Introductionmentioning
confidence: 96%
“…Regarding the association between sleep disturbance and behaviour, only one study has investigated this relationship in extremely preterm children [22]. Greater difficulties falling asleep or waking frequently were associated with greater emotional, conduct, hyperactivity/inattention and peer problems at age 11 years [22].…”
Section: Introductionmentioning
confidence: 99%